THE STATUS OF SOCIAL ACCOUNTING AND NATIONAL INCOME STATISTICS IN COUNTRIES OTHER THAN THE UNITED STATES. - Cooper, W. W.; Crawford, J. M. (The Accounting Review, 1953)
Abstract In this paper a distinction is drawn between national income statistics and social accounting, despite the close relation that exists between the two fields. The former field is viewed as being concerned with compilation and publication of isolated aggregate figures such as national income or gross national product which purport to provide over-all pictures of a nation's total economic activity. The latter field is concerned with details of structure and intra-sector flows in the context of a double-entry system of accounts. As a proper part of the system of social accounts various national income statistics may be synthesized. The purpose of a national system of accounts is to provide information concerning the economic activity of a country in concise and comprehensive fashion. This requires a systematic method of classifying economic transactions. This may be done in a variety of ways. One classification may be by type of economic activity, another classification may be by type of economic function and the formation of capital.